Body composition and dietary intake of energy giving nutrients among older age groups - Vaka Rögnvaldsdóttir 1976- (2011)
Introduction: Body composition and nutrition are important contributors to health. Deviations from a healthy body weight, both underweight and overweight, are associated with higher risk of health problems. Objectives: To investigate the association between body mass index (BMI), waist circumference (WC), and fat percentage categories and their association with macro-nutrient intake, fat free mass index (FFMI) and skeletal muscle mass index (SMI) among elderly Icelandic subjects. Design: Cross sectional study of macro-nutrient intake, body mass index (BMI), waist circumference (WC), body fat percentage, FFMI and SMI. Setting: Reykjavík city area and the urban area of Árborg. Participants: Senior citizens aged 64-91 years. The average woman (n=91) was 77.3 ±4.2 years of age, whereas the average age of the men (n=74) was 79.2 ±6.1 year. Measurements: Macro-nutrient intake was estimated by three-day dietary records. Baseline measurements of weight, height, BMI (split into normal-overweight and obesity), WC (split into three groups according to health risk), body fat percentage (split in tertiles), FFMI, SMI and the agility test “8 foot up and go” were used for analysis. Results: When divided into BMI groups there was no significant difference in the average intake of any macro-nutrient and BMI was neither associated with WC nor body fat percentage. Body fat percentage however increased with rising WC for both genders (p<0.001). FFMI had a positive relationship with BMI, WC and body fat percentage. The prevalence of sarcopenia was low, 2.2% and 10.3% for women and men respectively. For men there was a significant difference in dietary intake between the WC groups in consumption of added sugar kcal/day (p=0.047) and as E%(p=0.025), with the middle group having the highest intake. The women showed the same trend although not significant (p=0.181). Dietary fiber consumption had an inverse association with WC for both genders, but it was only significant among men (p=0.020). Protein consumption, calculated in g/kg ...